PERSEPSI DAN INTENSI PELAKU UMKM TERHADAP PENGGUNAAN QRIS SEBAGAI SISTEM PEMBAYARAN DIGITAL DI KOTA TASIKMALAYA - Santika, Alis; Aliyani, Ranti; Mintarsih, Ria (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research aims to determine the perceptions and intentions of SMEs towards the use of QRIS as a digital-based payment system in the City of Tasikmalaya. qualitative research approach through phenomenological design. The technique used is data triangulation, in the form of combining data sources obtained from observations, interviews, and documentation. The research sample consists of 10 SMEs in Tasikmalaya City that have used QRIS as a digital payment process. The indicators are used to see the perception of SMEs in terms of perceptions of benefits, perceptions of convenience, and perceptions of risk. The intentions of SMEs actors towards QRIS are also formed from the three perceptions accompanied by obstacles or obstacles and external factors that influence them. This study indicates that SMEs actors have a positive perception of QRIS so that they can form strong intentions for them to implement a digital payment system through QRIS.